O olhar afro-brasileiro de Mário de Andrade para o “irmaozão do Norte” no contexto do pan-americanismo - Grillo, Angela (Brasiliana: Journal for Brazilian Studies, 2019)
In the 1930s and 1940s, Brazilian intellectuals and artists – allied or persecuted by the Estado Novo – were enthusiastic about the Pan- Americanist proposals. Although insistently sought by US researchers Mário de Andrade, in turn, had a constant distrust of the “big brother of the north”. This article, based on a study of the social network of the time around the writer, explores the critical stance of the Afro-Brazilian Mario de Andrade towards the United States, in the context of Pan- Americanism. The knowledge that he acquired from cultures of African derivation, the recognition avant la lettre of a diasporic black identity and of racial violence set the tone of his unique interpretation of the “democratic paradise”.